POTENSI BAHAYA DAN RISIKO DENGAN METODE HIRADC PADA PROSES OPERASIONAL INDUSTRI PETROKIMIA PADA PERGANTIAN ADSORBENT 201-D PABRIK 1-B - MARIA AGNES TUTO RUING; ERRY YULIAN TRIBLAS ADESTA; ATIDIRA DWI HANANI (Universitas Mahasaraswati K. Mataram, 2024)
The implementation of HIRADC (Hazard Identification Risk Assessment and Determinant Control) is one of the efforts that can be made to control potential hazards that cause work accidents. HIRADC (Hazard Identification Risk Assessment and Determinant Control) is the process of identifying hazards, assessing, and evaluating the risks contained in work activities and environments. The results of the risk evaluation are used to determine hazard control efforts so that they can reduce the level of risk that is likely to cause work accidents. The method used to complete the research results has achieved the expected objectives. The data presented uses a qualitative descriptive approach, which shows K3 in accordance with current conditions, developing policies, ongoing processes, and effects that occur or trends that are occurring in the company. These results are compared with data obtained in the field or from the HSE regarding the implemen- tation procedure of HIRADC (Hazard Identification Risk Assessment and Determi- nant Control) and compared with applicable standards. Based on the identification that has been carried out, 42 potential hazards have been identified from 21 stages of work activities, 6 of which are in the high risk category, 20 are in the low risk category, 16 are in the medium risk category. Furthermore, all these activities or processes are then analyzed in the HIRADC table and converted into percentages for each category to determine the risk priority. The results for the low risk level are 0.47%, the medium risk level is 0.38%, and the high risk level is 0.14%. This company has made efforts to reduce potential hazards in the work environment through substitution, engineering control, administrative control, and finally PPE